PERBANDINGAN TINGKAT DISIPLIN SISWA YANG MENGIKUTI EKSTRAKURIKULER BOLA TANGAN DAN KARATE DALAM PELAJARAN PENJAS DI SMAN 24 BANDUNG - Rahmat, Asep (2014)
This study aims to know whether there are differences in the level of student's discipline between student who takes extracurricular Handball and Karate in Physical Education lesson at SMAN 24 Bandung. The method was used descriptive comparative research methods, purposive sampling research design. The population is the students of SMAN 24 Bandung who takes extracurricular of Handball and Karate a number of 30 students, while the 15 sample students from each extracurricular of Handball and Karate who was takes those extracurricular more than a years. A questionnaire using Likert scale was used as instrument in this study. The results of test of the level of discipline from the extracurricular of Handball and Karate obtained, score of Handball 2520 from maximal score 3150 or 80%. And score of Karate 2678 from maximal score 3150 or 85%. The conclusion is that there are the differences in the level of student's discipline who takes extracurricular of Handball and Karate in Physical Education lesson at SMAN 24 Bandung. In an indicator of students who takes extracurricular of Karate have higher level of discipline than students who takes extracurricular of Handball.